Pengaruh Locus of Control dan Lingkungan Kerja terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Tari Yulianda Putri; Maria Magdalena; Jeki Algusri (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to statistically prove the influence of locus of control and work environment on employee performance at the Padang City Population and Civil Registration Service. The sample method used in this research used a total sampling technique. The sample in this research were employees of the Padang City Population and Civil Registration Service using a questionnaire totaling 46 respondents. The types of data used in this research are primary data and secondary data. The primary data obtained were analyzed using multiple linear regression analysis tests. The technique for analyzing the data uses validity and reliability tests using the SPSS 21 program. The hypothesis is tested using the T test. The results of this research show (1) Locus of Control has a significant effect on employee performance at the Padang City Population and Civil Registration Service (2) The work environment has an effect significant impact on employee performance at the Padang City Population and Civil Registration Service.